If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y + 4 = 2(3y + 12) Reorder the terms: 4 + -2y = 2(3y + 12) Reorder the terms: 4 + -2y = 2(12 + 3y) 4 + -2y = (12 * 2 + 3y * 2) 4 + -2y = (24 + 6y) Solving 4 + -2y = 24 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 4 + -2y + -6y = 24 + 6y + -6y Combine like terms: -2y + -6y = -8y 4 + -8y = 24 + 6y + -6y Combine like terms: 6y + -6y = 0 4 + -8y = 24 + 0 4 + -8y = 24 Add '-4' to each side of the equation. 4 + -4 + -8y = 24 + -4 Combine like terms: 4 + -4 = 0 0 + -8y = 24 + -4 -8y = 24 + -4 Combine like terms: 24 + -4 = 20 -8y = 20 Divide each side by '-8'. y = -2.5 Simplifying y = -2.5
| 2.3x+13.2=1.52-(x-4.75) | | 100+10*2/5= | | 0=x^2-6x+24 | | 8x-23=x^2+2x+1 | | 24x+3= | | 3x^2-6xy+3y^2+10x-8y-2=0 | | 8x+3x-9x=4+4 | | 3g-2=g+8 | | -x-6-1+6x= | | 7(x+3)-7=4x+3(3+x) | | 5X-2X-28=32 | | 3(2n-5)=(8n+4)+6 | | 8X+4X-95=157 | | 4k+1-2k-2= | | -5(t-5)57t=8t-6 | | 5x+10=11x-11 | | 7(4x-9)+8=28x-55 | | 7x+10=13x-11 | | 3x+3x+1=128 | | 3r+5-r=7 | | 20(n+2)=4(10+5n) | | 3x+27=5+7x | | 0.4x+0.30(110)=0.20(125) | | 0.5f-3=1 | | 54x-8=0 | | -2y+2=-2(2y+7) | | 5.3x-3.46=7.1x+5.09 | | 81-2x=43x+21 | | -6y+4=2(4y+7) | | 2x^2+100x-1000=0 | | 2x^2+7x-140=0 | | 2x^2+4x-80=0 |